Ensuring tuberculosis treatment adherence with a mobile-based CARE-call system in Thailand: a pilot study. Issue 2 (1st February 2020) - Ratchakit-Nedsuwan, Ratchanit; Nedsuwan, Supalert; Sawadna, Vuddhichai; Chaiyasirinroje, Boonchai; Bupachat, Surasit; Ngamwithayapong-Yanai, Jintana; Kantima, Tassawan; Luangjina, Sarmwai; Boonyamanonukul, Pimporn; Wongyai, Jiraporn; Thawthong, Sureerat; Losuphakarn, Yongyut; et al.
Abstract: Background: Medication non-adherence in tuberculosis (TB) patients is an obstacle to TB treatment. Directly observed treatment to monitor and ensure adherence still has some limitations in high TB-burden countries. Most digital adherence technologies emphasize medication-taking reminder functions; however, a bi-directional communication platform to provide patient-health workers with an interface that focuses on enhancing medication adherence is likely to improve medical adherence. A budgeted mobile-based system called CARE-call providing both functions was developed and evaluated concerning whether it could enhance medication adherence. Design: Mixed methods combined quantitative and qualitative approaches. One hundred TB patients were randomized into intervention or control groups. Medication adherence rates between the two groups were compared. A focus group discussion was conducted to obtain in-depth perspectives from the patients. Results: At a 90% adherence level, the number of non-adherence patients in the intervention group was significantly lower than that of the control group (7.5% vs. 27.5%, p = .037). The participants were satisfied with the functions provided by the system, especially the confidentiality of the monitoring process, which did not involve monitoring by imaging or video recording. The bi-directional communication enabled them to contact health staff when concerns arose during the treatment course. Poor mobile phone signals and fast battery drain were reported as major technical problems of the system. Conclusions: The CARE-call system was able to prevent non-adherence in this rural setting in Thailand. However, further investigation with a larger sample size should be conducted on whether the system can also improve successful TB treatment outcome.